2014
DOI: 10.9790/0837-191090918
|View full text |Cite
|
Sign up to set email alerts
|

Urban Slum Characteristics in the Niger Delta Region of Nigeria: Imperatives for improvement

Abstract: Problems of urban environmental degradation and inadequacy of housing and basic infrastructural facilities in the Niger

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Despite the desired aim of residents of Port Harcourt slums to make ends meet through the different economic activities they are engaged in, violence is still witnessed. Clinard & Abbot as cited in Abotutu (2014) observed that slum housing has a significant degree of relationship with deviant behavior. This reveals that slum areas in Port Harcourt are areas where violence is rife.…”
Section: Urban Slum Violencementioning
confidence: 95%
“…Despite the desired aim of residents of Port Harcourt slums to make ends meet through the different economic activities they are engaged in, violence is still witnessed. Clinard & Abbot as cited in Abotutu (2014) observed that slum housing has a significant degree of relationship with deviant behavior. This reveals that slum areas in Port Harcourt are areas where violence is rife.…”
Section: Urban Slum Violencementioning
confidence: 95%